Comprehensive structural analysis of Al-incorporated Li7La3Zr2O12 - Yoo, Chung Yul; Lee, June Hyuk (Materials Letters, 2024)
The incorporation of Al in the Li7La3Zr2O12 (LLZO) structure was systematically investigated using X-ray/neutron powder diffraction and solid-state 27Al nuclear magnetic resonance. Pristine LLZO as well as 15 and 30 mol.% Al-incorporated LLZO materials were prepared by solid-state reaction. The X-ray diffraction patterns confirmed that the incorporation of 15 mol.% Al resulted in the formation of tetragonal LLZO upon calcination at 1000 °C; then, cubic LLZO was obtained after calcination at 1050 °C. In contrast, pristine and 30 mol.% Al-incorporated LLZO only exhibited a tetragonal structure. The detailed structure of 15 mol.% Al-incorporated LLZO was further analyzed by neutron powder diffraction and 27Al nuclear magnetic resonance. These analyses enabled to distinguish the crystal structures of tetragonal and cubic LLZO with similar lattice parameters, and to determine the lattice sites for Al incorporation in LLZO.
Keywords: Al incorporation; Crystals structures; Diffraction and scattering; Energy storage and conversions; Lattice sites; Phases transformation; Solid-state reactions; Tetragonal structure; X ray diffraction patterns; X-ray techniques; Energy storage and conversion; Neutron diffraction and scattering; Phase transformation; X-ray techniques